1991
DOI: 10.1128/iai.59.10.3708-3714.1991
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of enteric-coated protease in preventing attachment of enterotoxigenic Escherichia coli and diarrheal disease in the RITARD model

Abstract: In this study, we report on a novel approach based on modification of the intestinal surface to prevent diarrhea caused by enterotoxigenic Escherichia coli (ETEC). The removable intestinal tie adult rabbit diarrhea (RITARD) model was used to test the efficacy of an enteric-coated protease preparation (Detach; Enzacor Technology Pty. Ltd.) in the prevention of bacterial attachment and diarrheal disease caused by colonization factor antigen I-positive (CFA/I+) E. coli H10407. Protease was administered orally to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…However, there are potential concerns in the use of these animal models to study ETEC infections, namely, the inability of ETEC to elicit an immune response in the animal, adhere to and colonize the animal gut, and induce symptoms consistent with diarrhea, in addition to the resistance of the animal to ETEC with age. The removable intestinal tie adult rabbit diarrhea (RITARD) model has been used in the study of ETEC-induced acute diarrheal disease (Mynott et al, 1991), but this procedure is surgically invasive and hence is very stressful to the animal.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are potential concerns in the use of these animal models to study ETEC infections, namely, the inability of ETEC to elicit an immune response in the animal, adhere to and colonize the animal gut, and induce symptoms consistent with diarrhea, in addition to the resistance of the animal to ETEC with age. The removable intestinal tie adult rabbit diarrhea (RITARD) model has been used in the study of ETEC-induced acute diarrheal disease (Mynott et al, 1991), but this procedure is surgically invasive and hence is very stressful to the animal.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the role of the HA/protease in detachment merits further consideration from the standpoint of vaccine development (a vibrio which adheres longer is more likely to stimulate an effective immune response) and for its role in the ecology of V. cholerae (a vibrio which is prevented from detaching is less likely to cause devastating epidemics). Further, a recent study (28) indicated that pretreatment of rabbits with an enteric-coated protease preparation prevented intestinal colonization by E. coli. The HA/protease might similarly be useful as a prophylactic agent in preventing colonization by V. cholerae.…”
Section: Discussionmentioning
confidence: 99%
“…Brush border vesicles (BBV) were prepared from both rabbit (New Zealand White, 2.0 kg) and human jejunum. The jejunum was the pre-ferred site, as it had previously been shown in animal studies that this region was most heavily colonised by ETEC organisms and had the highest pilus receptor activity [31,32]. Specimens of human small intestine (approximately 2-5 cm in length) were obtained from adult patients and were provided by C.W.…”
Section: Epithelial Specimensmentioning
confidence: 99%
“…Specific antisera against CFA were produced as previously described [32]. Antisera directed against human preparations were raised in paired rabbits contained in isolation unit facilities at Fairfield Infectious Diseases hospital (Fairfield, Victoria, Australia) to avoid any risk from viral/bacterial contaminants which could theoretically have been present.…”
Section: Antiseramentioning
confidence: 99%